Active Materiality sebagai Basis Perancangan Arsitektur dalam Merespons Polusi - Ruth Kartika Purnasasmita; Yandi Andri Yatmo; Paramita Atmodiwirjo (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
This paper describes the architectural design process based on an understanding of living materials’ properties and their growth process in response to pollution. The development of the design method was based on the existence of living materials and their potential to be the active unit of architecture. Living materials could actively grow and adapt through their reactions to external factors, in this case, pollution, allowing the material to be in a passive phase temporarily due to the forces. This paper focuses on the development of design methods based on the understanding of algae, fungi, and lichen as the living materials that will detect and detoxify air and soil pollution around Daan Mogot, West Jakarta. By conducting research through design, this paper then proposes architectural design by injecting the active-passive growth process of living materials (algae, fungi, and lichen) into the context using split and absorb mechanisms. In response to pollution, the active and passive schemes of living materials become the foundation of architectural design. This paper then proposes the term